Active power optimization based on non adaptive immune algorithm: article - Md. Saleh, Nurhayati; Musirin, Ismail (2010)
This paper presents a study of active power optimization based on non adaptive immune algorithm (NAIA) in power systems. The aim of active power optimization is to reduce the power loss by controlling the active power scheduling on the generators. Simulations are carried out on standard IEEE 30-bus system and results are presented. All the process and development is done using MATLAB 7.0. Result obtained from the simulation indicated that the developed engine managed to minimize the losses in the system.